Rehab VR - Elangovan, Khartick Raj (IRC, 2019)
Final Year Project (FYP) is an initiative that every student needs to complete before being allowed to graduate from Universiti Teknologi Petronas (UTP). This proposal is written for the development of Rehab VR, a home-based stroke rehabilitation system for Universiti Teknologi Petronas (UTP). As we know, stroke is one of the most dangerous diseases out there. The traditional rehabilitation system that we have now is not as effective as modern systems. To complete this project, two phases of methodology are being use which are preliminary studies and system development. To conduct the preliminary studies, literature review of the project and interviews the stakeholders will be done. For system development, I decided to use the Scrum methodology with a lean approach. With that, I have gathered initial drafts of the interfaces and modules.